Beyond Field Studies: An analogue comparison of NICHD and MoGP forensic interview guidelines in children’s testimony - Pérez Cano, Mario; Priero Redín, Ángel; García Sánchez, Manuel; Meseguer Aragon, Judith (Anales de Psicología / Annals of Psychology, 2026)
This analogue study compares the effectiveness of two forensic interview protocols—the NICHD Protocol and the Memorandum of Good Practice (MoGP)—in eliciting accurate and forensically relevant information from children. A total of 123 children (60 aged 6–7 and 63 aged 10–11) participated in a staged event, followed by a delayed interview conducted using either the NICHD or MoGP guidelines. Interviewers were postgraduate students who received protocol-specific training. Transcripts were coded for prompt type and the amount, accuracy, and relevance of elicited details. Generalized linear mixed models revealed that interviews conducted using the NICHD Protocol elicited more total, correct, central, and peripheral details, particularly through invitations and cued invitations. Option-posing prompts were the least effective, yielding the fewest correct and peripheral details. Age-related differences in productivity and accuracy were attenuated after controlling for the informativeness of prompt types. Option-posing questions were frequently used in both conditions, including NICHD-guided interviews. These findings highlight the critical role of prompt formulation in shaping children’s narrative responses and underscore the relative advantages of the NICHD Protocol. They further suggest that enhanced interviewer training is needed to reduce reliance on less effective prompt types and to promote best practices in investigative interviewing.